Factors affecting retention and relapse in orthodontics - Najjar, Hussam E.; Alasmari, Renad Mohammed; Manie, Asrar Mohammed Al; Balbaid, Khalid Nassir; Alzaher, Kuthar Hassan; Assiri, Ashwaq Talal; Alqarni, Sundus Saad; Turkistani, Abdullah Abdul Aziz; Anzi, Sarah Khalid Al; Alkhudhayr, Bassam Abdullah; Alfaifi, Shatha Ahmed (International Journal Of Community Medicine And Public Health, 2023)
Orthodontic treatment aims to achieve stable and harmonious occlusion by correcting malocclusions and aligning teeth. However, the long-term success of orthodontic treatment relies heavily on the effectiveness of the retention phase. Retention involves maintaining the corrected tooth positions and preventing relapse, which refers to the tendency of teeth to return to their original maloccluded positions over time. The retention phase applied after treatment is important to obtain stable results. Various factors can influence the retention phase and contribute to relapse in orthodontics. Periodontium, soft tissue pressures, growth, and occlusion are among these factors affecting stability. Understanding these factors is crucial for orthodontists to design appropriate retention protocols and enhance treatment outcomes. To achieve successful long-term stability, orthodontists must comprehensively evaluate and address the factors during the retention phase. This review article will discuss factors that affect retention and relapse in orthodontics.